Knowledge Management Strategy and Initiative for Development of Digital Energy Hub - Bin Kasim, Hairoladenan; ., .; ., . (International Journal of Engineering and Technology, 2018)
This article revised several Knowledge Management (KM) strategies and initiatives, in order to develop the digital energy hub. This digital platform employs robust computers and network technology to cater for a wide-range exchange of information and knowledge, which eventually supports new businesses, collaboration and globalization for the energy players. The objective of this article is to analyze KM strategy and initiative for the purpose of developing a digital energy hub. Among the important strategies are goal setting, KM leadership, structure and skill; supported by essential initiatives such as knowledge creation, transfer and sharing.Â  Thus, by accurately identifying the relevant KM strategies and initiatives, the probability for future development and deployment of this platform to be successful can be enhanced.Â